The classic and universal values: A discussion from the foundations of historical-critical pedagogy - Ferreira, Carolina Góis [UNESP]; Duarte, Newton [UNESP] (Universidade Estadual de Maringa, 2021)
This paper aims to develop relationships between the concept of classic, as postulated by historical-critical pedagogy and the constitution of universal values. In order to achieve this goal, the text is divided in three parts. Firstly, we discuss the counterpoint between the conception of knowledge present in historical-critical pedagogy and the conception of hegemonic knowledge. Secondly, based on the works of Karl Marx (1818-1883) and Friedrich Engels (1820-1895), productions by György Lukács (1885-1971) and authors close to his thinking, such as Agnes Heller (1929-2019) and György Márkus (1934-2016), we seek to establish the relations between the construction of universal values and the classic. Lastly, in the third part, we analyze educational work as a process situated in the scope of school education and linked to the preservation of universal values condensed in classic knowledge. We observed that the understandingof the classic based on the constitution of universal values is fundamental to an understanding of its conformation as a product of human activity. The values condensed in classic knowledge, beyond the social-historical link, transcend towards universality. The adequate comprehension of this process allows us to overcome the antinomy between dogmatism and relativism, a fundamental condition to understanding the concept of classic as postulated by historical-critical pedagogy.
El clásico y los valores universales: Una discusión desde los fundamentos de la pedagogía histórico-crítica
Keywords: Classic; Historical-critical pedagogy; Marxism; School education